Comparing loss-on-ignition, acid decarbonation and combustion elemental analysis for measuring organic carbon concentrations – recommendations for best practice - Robert B. Sparkes; Stuart A. Rae; Lucy McMahon; Hannah L. Mossman; David McKendry; Clare E. Dean; Graham Tinsley; Frances Fowden; Connor J. Grisdale; Hafiza Begum; Holly Hope; Charlotte McEnhill; et al. (Organic Geochemistry, 2026)

Selective Receptor Modulation by Truncated Neuropeptide Y (3–36) Dissociates Vasoconstriction from Neuroprotection in Experimental Glaucoma - Viswanthram Palanivel; Devaraj Basavarajappa; Akanksha Salkar; András M. Komáromy; Ole Tietz; Taslima Akter Eva; Nitin Chitranshi; Mehdi Mirzaei; Veer Gupta; Yuyi You; Stuart L. Graham; Vivek Gupta (Molecular Neurobiology, 2026)

The Dynamic Roles of Repressor Element 1-Silencing Transcription Factor (REST): A Double-Edged Sword in Neural Health and Disease - Taslima Akter Eva; Avinash Shenoy; Veer B. Gupta; Viswanthram Palanivel; Akanksha Salkar; Sohrab Nowroozi Nasab; Nitin Chitranshi; Mehdi Mirzaei; Yuyi You; Stuart L. Graham; Devaraj Basavarajappa; Vivek Gupta (Molecular Neurobiology, 2026)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Correlations between postmortem quantitative MRI parameters and demyelination, axonal loss and gliosis in multiple sclerosis: A systematic review and meta-analysis - Ting Shen; Samran Sheriff; Yanlin Qu; Vivek K. Gupta; Stuart L. Graham; Alexander Klistorner; Huixun Jia; Xiaodong Sun; Yuyi You (Brain Imaging and Behavior, 2025)

Unifying Coral Reef States Through Space and Time Reveals a Changing Ecosystem - Simon J. Brandl; Jérémy Carlot; Rick D. Stuart‐Smith; Sally A. Keith; Nicholas A. J. Graham; Graham J. Edgar; Jérémy Wicquart; Shaun K. Wilson; Rucha Karkarey; Mary K. Donovan; Jesus E. Arias‐Gonzalez; Rohan Arthur; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological state shifts that alter the structure and function of entire ecosystems are a concerning consequence of human impact. Yet, when, where and why discrete ecological states emerge remains difficult to predict and monitor, especially in high‐diversity systems. We sought to quantify state shifts and their drivers through space and time in the most ecologically complex marine ecosystem: tropical coral reefs. Location Worldwide. Time Period 1987–2019. Major Taxa Studied Coral reef communities. Methods Using a global dataset of 3375 coral reef surveys, along with 13 time series datasets ranging between 1987 and 2019, we applied a novel double‐dichotomy approach to classify coral reefs into four simplified and discrete states based on the relative contributions of corals versus algae to benthic cover and small‐bodied versus large‐bodied fishes to fish standing stock. We then examined state shifts considering a range of spatial predictors and tested whether states have shifted directionally over time, and the nature of the most common transitions. Results We show that geographic, environmental and anthropogenic context fundamentally shapes coral reef states at the local scale, which explains disparities among case studies, and stakes out critical baseline expectations for regional management efforts. We also reveal clear multi‐decadal state shifts on coral reefs: over time, systems dominated by reef‐building corals and small‐bodied, planktivorous fishes tend to have been replaced with reefs characterised by algae and larger‐bodied fishes. Main Conclusions Our results suggest a previously unrecognised transition from systems that harness external subsidies through small‐bodied consumers associated with structurally complex live corals, to herbivore‐dominated systems with stronger bottom‐up dynamics. Overall, the partitioning of complex reef ecosystems into a small suite of discrete ecological states suggests that spatial context‐dependency, shifting baselines and changes in reef functioning are crucial considerations for coral reef management in the 21st century.

Rapid remote volcanic ashfall impact assessment for the 2022 eruption of Hunga volcano, Tonga: a bespoke approach and lessons identified - Alana M. Weir; James H. Williams; Thomas M. Wilson; Josh L. Hayes; Carol Stewart; Graham S. Leonard; Christina Magill; Susanna F. Jenkins; Shaun Williams; Heather M. Craig; Taaniela Kula; Stuart Fraser; et al. (Bulletin of Volcanology, 2024)
When disasters occur, rapid impact assessments are required to prioritise response actions, support in-country efforts and inform the mobilisation of aid. The 15 January 2022 eruption of Hunga volcano, Tonga, and the resulting atmospheric shockwave, ashfall, underwater mass disturbance and tsunami, caused substantial impacts across the Kingdom of Tonga. Volcanic impacts on the scale observed after the eruption are rare, necessitating a reliance on international advice and assistance. The situation was complicated by the loss of Tonga’s international submarine fibreoptic cable (causing a complete loss of communications for approximately 20 days) along with border closures due to the COVID-19 pandemic. A need emerged for a rapid remote volcanic impact assessment and provision of specialist advice to help inform the response of international partners. Here we present a novel methodology for conducting rapid remote volcanic ashfall impact assessments, conducted over a 10-day period following the eruption. We used three different hazard models for ashfall thickness across the main island of Tongatapu and available asset information and vulnerability functions for buildings, agriculture, electricity networks, water supply and roads, to provide initial estimates of losses due to ashfall from the 15 January eruption. For buildings, we estimated losses both as total losses and as percentages of the total replacement cost of buildings on Tongatapu. For agriculture, we made probabilistic estimates of production losses for three different crop classes. For ashfall clean-up, we estimated ranges of ashfall volumes requiring clean-up from road surfaces and roofs. For water supply, electricity networks and roads, our analysis was limited to assessing the exposure of important assets to ashfall, as we had insufficient information on system configurations to take the analysis further. Key constraints on our analysis were the limited nature of critical infrastructure asset inventories and the lack of volcanic vulnerability models for tropical regions including Pacific Island nations. Key steps towards iteratively improving rapid remote impact assessments will include developing vulnerability functions for tropical environments as well as ground-truthing estimated losses from remote approaches against in-person impact assessment campaigns.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Mean reef fish body size decreases towards warmer waters - Amy Rose Coghlan; Julia L. Blanchard; Simon Wotherspoon; Rick D. Stuart‐Smith; Graham J. Edgar; Neville Barrett; Asta Audzijonyte (Ecology Letters, 2024)
Aquatic ectotherms often attain smaller body sizes at higher temperatures. By analysing ~15,000 coastal‐reef fish surveys across a 15°C spatial sea surface temperature (SST) gradient, we found that the mean length of fish in communities decreased by ~5% for each 1°C temperature increase across space, or 50% decrease in mean length from 14 to 29°C mean annual SST. Community mean body size change was driven by differential temperature responses within trophic groups and temperature‐driven change in their relative abundance. Herbivores, invertivores and planktivores became smaller on average in warmer temperatures, but no trend was found in piscivores. Nearly 25% of the temperature‐related community mean size trend was attributable to trophic composition at the warmest sites, but at colder temperatures, this was

Anti-inflammatory Effects of Siponimod in a Mouse Model of Excitotoxicity-Induced Retinal Injury - Devaraj Basavarajappa; Vivek Gupta; Nitin Chitranshi; Deepa Viswanathan; Veer Gupta; Roshana Vander Wall; Viswanthram Palanivel; Mehdi Mirzaei; Yuyi You; Alexander Klistorner; Stuart L. Graham (Molecular Neurobiology, 2023)
Glaucoma is a leading cause of permanent blindness worldwide and is characterized by neurodegeneration linked to progressive retinal ganglion cell (RGC) death, axonal damage, and neuroinflammation. Glutamate excitotoxicity mediated through N-methyl-D-aspartate (NMDA) receptors plays a crucial role in glaucomatous RGC loss. Sphingosine 1-phosphate receptors (S1PRs) are important mediators of neurodegeneration and neuroinflammation in the brain and the retina. Siponimod is an immunomodulatory drug for multiple sclerosis and is a selective modulator of S1PR subtypes 1 and 5 and has been shown to have beneficial effects on the central nervous system (CNS) in degenerative conditions. Our previous study showed that mice administered orally with siponimod protected inner retinal structure and function against acute NMDA excitotoxicity. To elucidate the molecular mechanisms behind these protective effects, we investigated the inflammatory pathways affected by siponimod treatment in NMDA excitotoxicity model. NMDA excitotoxicity resulted in the activation of glial cells coupled with upregulation of the inflammatory NF-kB pathway and increased expression of TNFα, IL1-β, and IL-6. Siponimod treatment significantly reduced glial activation and suppressed the pro-inflammatory pathways. Furthermore, NMDA-induced activation of NLRP3 inflammasome and upregulation of neurotoxic inducible nitric oxide synthase (iNOS) were significantly diminished with siponimod treatment. Our data demonstrated that siponimod induces anti-inflammatory effects via suppression of glial activation and inflammatory singling pathways that could protect the retina against acute excitotoxicity conditions. These findings provide insights into the anti-inflammatory effects of siponimod in the CNS and suggest a potential therapeutic strategy for neuroinflammatory conditions.

Why humans kill animals and why we cannot avoid it - Benjamin L. Allen; Christopher Bobier; Stuart Dawson; Peter J.S. Fleming; Jordan Hampton; David Jachowski; Graham I.H. Kerley; John D.C. Linnell; Kelly Marnewick; Liaan Minnie; Mike Muthersbaugh; M. Justin O'Riain; et al. (Science of The Total Environment, 2023)

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Spatial compositional turnover varies with trophic level and body size in marine assemblages of micro‐ and macroorganisms - Amanda K. Pettersen; Melinda A. Coleman; Guillaume Latombe; Sebastian Vadillo Gonzalez; Nathan L. R. Williams; Justin R. Seymour; Alexandra H. Campbell; Torsten Thomas; Renata Ferrari; Rick D. Stuart‐Smith; Graham J. Edgar; Peter D. Steinberg; et al. (Global Ecology and Biogeography, 2022)
Aim Spatial compositional turnover varies considerably among co‐occurring assemblages of organisms, presumably shaped by common processes related to species traits. We investigated patterns of spatial turnover in a diverse set of marine assemblages using zeta diversity, which extends traditional pairwise measures of turnover to capture the roles of both rare and common species in shaping assemblage turnover. We tested the generality of hypothesized patterns related to ecological traits and provide insights into mechanisms of biodiversity change. Location Temperate pelagic and benthic marine assemblages of micro‐ and macroorganisms along south‐eastern Australia (30–36° S latitude). Time period 2008–2021. Major taxa studied Bacteria, phytoplankton, zooplankton, fish, and macrobenthic groups. Methods Six marine datasets spanning bacteria to fishes were collated for measures of “species” occurrence, with a 1° latitude grain. For each assemblage, ecological traits of body size, habitat and trophic level were analysed for the form and rate of decline in zeta diversity and for the species retention rate. Results Species at higher trophic levels showed two to three times the rate of zeta diversity decline compared with lower trophic levels, indicating an increase in turnover from phytoplankton to carnivorous fishes. Body size showed the hypothesized unimodal relationship with rates of turnover for macroorganisms. Patterns of bacterial turnover contrasted with those found for macroorganisms, with the highest levels of turnover in pelagic habitats compared with benthic (kelp‐associated) habitats. The shape of retention rate curves showed the importance of both rare and common species in driving turnover; a finding that would not have been observable using pairwise (beta diversity) measures of turnover. Main conclusions Our results support theoretical predictions for phytoplankton and macroorganisms, showing an increase in turnover rate with trophic level, but these predictions did not hold for bacteria. Such deviations from theory need to be investigated further to identify underlying processes that govern microbial assemblage dynamics.

Correction to: Retinoid X Receptor: Cellular and Biochemical Roles of Nuclear Receptor with a Focus on Neuropathological Involvement - Samridhi Sharma; Ting Shen; Nitin Chitranshi; Veer Gupta; Devaraj Basavarajappa; Soumalya Sarkar; Mehdi Mirzaei; Yuyi You; Wojciech Krezel; Stuart L. Graham; Vivek Gupta (Molecular Neurobiology, 2022)

Retinoid X Receptor: Cellular and Biochemical Roles of Nuclear Receptor with a Focus on Neuropathological Involvement - Samridhi Sharma; Ting Shen; Nitin Chitranshi; Veer Gupta; Devaraj Basavarajappa; Soumalya Sarkar; Mehdi Mirzaei; Yuyi You; Wojciech Krezel; Stuart L. Graham; Vivek Gupta (Molecular Neurobiology, 2022)
Retinoid X receptors (RXRs) present a subgroup of the nuclear receptor superfamily with particularly high evolutionary conservation of ligand binding domain. The receptor exists in α, β, and γ isotypes that form homo-/heterodimeric complexes with other permissive and non-permissive receptors. While research has identified the biochemical roles of several nuclear receptor family members, the roles of RXRs in various neurological disorders remain relatively under-investigated. RXR acts as ligand-regulated transcription factor, modulating the expression of genes that plays a critical role in mediating several developmental, metabolic, and biochemical processes. Cumulative evidence indicates that abnormal RXR signalling affects neuronal stress and neuroinflammatory networks in several neuropathological conditions. Protective effects of targeting RXRs through pharmacological ligands have been established in various cell and animal models of neuronal injury including Alzheimer disease, Parkinson disease, glaucoma, multiple sclerosis, and stroke. This review summarises the existing knowledge about the roles of RXR, its interacting partners, and ligands in CNS disorders. Future research will determine the importance of structural and functional heterogeneity amongst various RXR isotypes as well as elucidate functional links between RXR homo- or heterodimers and specific physiological conditions to increase drug targeting efficiency in pathological conditions.

Connecting to the oceans: supporting ocean literacy and public engagement - Rachel Kelly; Karen Evans; Karen Alexander; Silvana Bettiol; Stuart Corney; Coco Cullen-Knox; Christopher Cvitanovic; Kristy de Salas; Gholam Reza Emad; Liam Fullbrook; Carolina Garcia; Sierra Ison; et al. (Reviews in Fish Biology and Fisheries, 2022)

Reef communities show predictable undulations in linear abundance size spectra from copepods to sharks - Freddie J. Heather; Rick D. Stuart‐Smith; Julia L. Blanchard; Kate M. Fraser; Graham J. Edgar (Ecology Letters, 2021)
Among the more widely accepted general hypotheses in ecology is that community relationships between abundance and body size follow a log‐linear size spectrum, from the smallest consumers to the largest predators (i.e. ‘bacteria to whales’). Nevertheless, most studies only investigate small subsets of this spectrum, and note that extreme size classes in survey data deviate from linear expectations. In this study, we fit size spectra to field data from 45 rocky and coral reef sites along a 28° latitudinal gradient, comprising individuals from 0.125 mm to 2 m in body size. We found that 96% of the variation in abundance along this ‘extended’ size gradient was described by a single linear function across all sites. However, consistent ‘wobbles’ were also observed, with subtle peaks and troughs in abundance along the spectrum, which varied with sea temperature, as predicted by theory relating to trophic cascades.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Globally consistent reef size spectra integrating fishes and invertebrates - Freddie J. Heather; Julia L. Blanchard; Graham J. Edgar; Rowan Trebilco; Rick D. Stuart‐Smith (Ecology Letters, 2021)
The frequency distribution of individual body sizes in animal communities (i.e. the size spectrum) provides powerful insights for understanding the energy flux through food webs. However, studies of size spectra in rocky and coral reef communities typically focus only on fishes or invertebrates due to taxonomic and data constraints, and consequently ignore energy pathways involving the full range of macroscopic consumer taxa. We analyse size spectra with co‐located fish and mobile macroinvertebrate data from 3369 reef sites worldwide, specifically focusing on how the addition of invertebrate data alters patterns. The inclusion of invertebrates steepens the size spectrum, more so in temperate regions, resulting in a consistent size spectrum slope across latitudes, and bringing slopes closer to theoretical expectations based on energy flow through the system. These results highlight the importance of understanding contributions of both invertebrates and fishes to reef food webs worldwide.

Caveolin-1 Ablation Imparts Partial Protection Against Inner Retinal Injury in Experimental Glaucoma and Reduces Apoptotic Activation - Mojdeh Abbasi; Vivek K. Gupta; Nitin Chitranshi; Veer B. Gupta; Mehdi Mirzaei; Yogita Dheer; Linda Garthwaite; Thiri Zaw; Robert G. Parton; Yuyi You; Stuart L. Graham (Molecular Neurobiology, 2020)

Upregulation of Proteolytic Pathways and Altered Protein Biosynthesis Underlie Retinal Pathology in a Mouse Model of Alzheimer’s Disease - Mehdi Mirzaei; Kanishka Pushpitha; Liting Deng; Nitin Chitranshi; Veer Gupta; Rashi Rajput; Abu Bakr Mangani; Yogita Dheer; Angela Godinez; Matthew J. McKay; Karthik Kamath; Dana Pascovici; et al. (Molecular Neurobiology, 2019)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Bexarotene Modulates Retinoid-X-Receptor Expression and Is Protective Against Neurotoxic Endoplasmic Reticulum Stress Response and Apoptotic Pathway Activation - Yogita Dheer; Nitin Chitranshi; Veer Gupta; Mojdeh Abbasi; Mehdi Mirzaei; Yuyi You; Roger Chung; Stuart L. Graham; Vivek Gupta (Molecular Neurobiology, 2018)

Soil drivers of local‐scale tree growth in a lowland tropical forest - Graham Zemunik; Stuart J. Davies; Benjamin L. Turner (Ecology, 2018)
Soil nutrients influence the distribution of tree species in lowland tropical forests, but their effect on productivity, especially at local scales, remains unclear. We used tree census, canopy occupancy, and soil data from the Barro Colorado Island (BCI; Panama) 50‐ha forest dynamics plot to investigate the influence of soil nutrients and potential toxins on aboveground tree productivity. Growth was calculated as the increase in diameter of 150,000 individual stems ≥1 cm diameter at breast height, representing 207 species. The effects of soil variables and other strong predictors of growth (e.g., light) were estimated using hierarchical, linear, mixed‐effects models. Growth was weakly positively associated with phosphorus (P), particularly for understory tree species that are typically considered to be limited by light. In contrast, growth was strongly negatively related to manganese (Mn) and aluminum (Al), although the latter effect was confounded by strong correlations between Al and other soil variables. The negative response to increasing Mn (and Al) suggests a toxicity effect due to solubilization and uptake of amorphous pools of metal oxides in the soil. These results show that P limits tropical tree growth at local scale on BCI, but that toxic metals represent an even greater constraint on productivity.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Intakes of fat and micronutrients between ages 13 and 18 years and the incidence of proliferative benign breast disease - Xuefen Su; Caroline E. Boeke; Laura C. Collins; Heather J. Baer; Walter C. Willett; Stuart J. Schnitt; James L. Connolly; Bernard Rosner; Graham A. Colditz; Rulla M. Tamimi (Cancer Causes & Control, 2015)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

Protective Effects of 7,8-Dihydroxyflavone on Retinal Ganglion and RGC-5 Cells Against Excitotoxic and Oxidative Stress - Vivek K. Gupta; Yuyi You; Jonathan C. Li; Alexander Klistorner; Stuart L. Graham (Journal of Molecular Neuroscience, 2013)

Non-invasive Estimation of Cerebrospinal Fluid Pressure Waveforms by Means of Retinal Venous Pulsatility and Central Aortic Blood Pressure - S. Mojtaba Golzan; Mi Ok Kim; Amir Saied Seddighi; Alberto Avolio; Stuart L. Graham (Annals of Biomedical Engineering, 2012)

Lifetime physical activity and the incidence of proliferative benign breast disease - Michelle M. Jung; Graham A. Colditz; Laura C. Collins; Stuart J. Schnitt; James L. Connolly; Rulla M. Tamimi (Cancer Causes & Control, 2011)

Intake of fiber and nuts during adolescence and incidence of proliferative benign breast disease - Xuefen Su; Rulla M. Tamimi; Laura C. Collins; Heather J. Baer; Eunyoung Cho; Laura Sampson; Walter C. Willett; Stuart J. Schnitt; James L. Connolly; Bernard A. Rosner; Graham A. Colditz (Cancer Causes & Control, 2010)